The Effect of Shopping Lifestyle, Risk Perception, and Price on Purchase Decisions of Fake Luxury Bags - Ringo, Vebyla Ronaria Br Siringo; Nuvriasari, Audita (LifeSciFi, 2024)
This study aims to analyze the influence of Shopping Lifestyle, Risk Perception, and Price on Purchase Decisions for Counterfeit Luxury Brands Charles and Keith Bags. The sample in this study was 100 respondents who purchased Counterfeit Luxury Brands Charles and Keith Bags online in the marketplace. The sampling technique used was purposive sampling. The data analysis tool used Multiple Linear Regression Analysis. The results of the study prove shopping Lifestyle has a positive and significant effect on purchase decisions for counterfeit luxury brands Charles and Keith bags. Risk Perception has a negative and significant effect on purchase decisions for counterfeit luxury brands Charles and Keith bags. Price has a positive and significant effect on purchase decisions for counterfeit luxury brands Charles and Keith bags.